Biomimetic microbeads containing a chondroitin sulfate/chitosan polyelectrolyte complex for cell-based cartilage therapy. Issue 40 (3rd August 2015) - Daley, Ethan L. H.; Coleman, Rhima M.; Stegemann, Jan P.
Abstract : Cell-encapsulating microbeads containing a biomimetic chondroitin sulfate–chitosan polyelectrolyte complex for cartilage tissue engineering. Abstract : Articular cartilage has a limited healing capacity that complicates the treatment of joint injuries and osteoarthritis. Newer repair strategies have focused on the use of cells and biomaterials to promote cartilage regeneration. In the present study, we developed and characterized bioinspired materials designed to mimic the composition of the cartilage extracellular matrix. Chondroitin sulfate (CS) and chitosan (CH) were used to form physically cross-linked macromolecular polyelectrolyte complexes (PEC) without the use of additional crosslinkers. A single-step water-in-oil emulsification process was used to either directly embed mesenchymal stem cells (MSC) in PEC particles created with various concentrations of CS and CH, or to co-embed MSC with PEC in agarose-based microbeads. Direct embedding of MSC in PEC resulted in high cell viability but irregular and large particles. Co-embedding of PEC particles with MSC in agarose (Ag) resulted in uniform microbeads 80–90 μm in diameter that maintained high cell viability over three weeks in culture. Increased serum content resulted in more uniform PEC distribution within the microbead matrix, and both high and low CS : CH ratios resulted in more homogeneous microbeads than 1 : 1 formulations. Under chondrogenic conditions, expression of sulfated GAG and collagen type II was increased in 10 : 1 CS : CH PEC–Ag microbeads compared to pure Ag beads, indicating a chondrogenic influence of the PEC component. Such PEC–Ag microbeads may have utility in the directed differentiation and delivery of progenitor cell populations for cartilage repair.